Possibility and Challenges of Conversion of Current Virus Species Names to Linnaean Binomials - Postler, Thomas S. (2016)
Botanical, mycological, zoological, and prokaryotic species names follow the Linnaean format, consisting of an italicized Latinized binomen with a capitalized genus name and a lower-case species epithet (e.g., Homo sapiens). Virus species names, however, do not follow a uniform format, and even when binomial, are not Linnaean in style. In this thought exercise, we attempted to convert all currently official names of species included in the virus family Arenaviridae and the virus order Mononegavirales to Linnaean binomials, and to identify and address associated challenges and concerns. Surprisingly, this endeavor was not as complicated or time-consuming as even the authors of this article expected when conceiving the experiment.